SCREENING ANEMIA PADA IBU HAMIL DI PUSKESMAS BERNUNG KABUPATEN PESAWARAN LAMPUNG - Yeti Septiasari; Dzul Istiqomah Hasyim; Nurwinda Saputri (LP4MK STKIP PGRI Lubuklinggau, 2020)
Anemia is a condition in which the number and size of red blood cells or concentrations of hemoglobin fall below the established cut-off value, consequently damaging the blood's capacity to transport oxygen throughout the body. Anemia in pregnancy is a maternal condition with hemoglobin (Hb) levels < 11 gr% in the I and III trimesters while in the second trimester hemoglobin levels < 10.5 gr%. Pregnancy anemia is called